Data Visualization on Interactive Surfaces: A Research Agenda from the DEXIS Workshop - Isenberg, Petra; Isenberg, Tobias; Hesselmann, Tobias; Lee, Bongshin; Zadow, Ulrich von, Anthony Tang (IEEE Computer Graphics and Applications, Institute of Electrical and Electronics Engineers, 2013)
Interactive tabletops and surfaces (ITSs) provide rich opportunities for data visualization and analysis and consequently are used increasingly in such settings. A research agenda of some of the most pressing challenges related to visualization on ITSs emerged from discussions with researchers and practitioners in human-computer interaction, computer-supported collaborative work, and a variety of visualization fields at the 2011 Workshop on Data Exploration for Interactive Surfaces (Dexis 2011)